2003
DOI: 10.2355/isijinternational.43.7
|View full text |Cite
|
Sign up to set email alerts
|

Standard Gibbs Free Energy of Formation of MnO-saturated MnO Cr2O3 Solid Solution at 1873K.

Abstract: The values of DG°and DG°f , MnO · Cr 2 O 3 are independent of the oxygen partial pressure within the P O 2 range in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Also, the magnesiochromite peaks are observed in conjunction with those of manganochromite or dicalcium silicate. It is interesting that the manganochromite peaks are nearly identical to those of synthetic MnCr 2 O 4 , which were recently reported by Tanahashi et al [24] This qualitatively means that the spinel phase observed in the present study would be identified as [Mn,Mg]Cr 2 O 4 including small amounts of Fe 2+ in the tetrahedral site from the observed results using EPMA (Fig. 2), EDS (Fig.…”
Section: Mineralogy Of the Cao-sio 2 -Cro X -Mgo-mno Slagssupporting
confidence: 80%
See 1 more Smart Citation
“…Also, the magnesiochromite peaks are observed in conjunction with those of manganochromite or dicalcium silicate. It is interesting that the manganochromite peaks are nearly identical to those of synthetic MnCr 2 O 4 , which were recently reported by Tanahashi et al [24] This qualitatively means that the spinel phase observed in the present study would be identified as [Mn,Mg]Cr 2 O 4 including small amounts of Fe 2+ in the tetrahedral site from the observed results using EPMA (Fig. 2), EDS (Fig.…”
Section: Mineralogy Of the Cao-sio 2 -Cro X -Mgo-mno Slagssupporting
confidence: 80%
“…1). Tanahashi et al [24] observed that the composition of the MnCr 2 O 4 phase equilibrating with liquid iron at 1873 K changes to [Mn 1-x Fe x ]Cr 2 O 4 as the oxygen partial pressure changes. That is, the value of x increases from about 0.03 to 0.09 by increasing the oxygen partial pressure from about pO 2 = 2.5 × 10 −11 to 5.0 × 10 −10 atm during their experiments.…”
Section: Mineralogy Of the Cao-sio 2 -Cro X -Mgo-mno Slagsmentioning
confidence: 98%
“…In the present investigation, the recent value for enthalpy of formation is adopted for MnCr 2 O 4 [22,23]. Our value on SrCrO 4 based on Dellian et al [25] compilation, that is, enthalpy of Shidlovskii et al [26] together with a larger entropy value are more negative than Maruyama et al [27] and Jacob and Abraham [28].…”
Section: Chromium Thermochemistrymentioning
confidence: 92%
“…The most recent investigation is from Tanahashi et al[37] who derived G Jacob et al[43] used the same technique as Tsai and Muan[39] and calculated the standard Gibbs energy changes at 1373 K for Eq. (9) using the activity data for the spinel phase obtained in their study and data for the corundum phase from a previous work[44] on the Al2O3-Cr2O3 system.…”
mentioning
confidence: 99%